2015
DOI: 10.3356/rapt-49-04-429-440.1
|View full text |Cite
|
Sign up to set email alerts
|

Space Use and Habitat Selection by Adult Migrant Golden Eagles Wintering in the Western United States

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
3
12
0
1
Order By: Relevance
“…NA golden eagles exhibit a variety of migration strategies. Segments of the population undergo long annual migrations from Alaska and northern Canada [32,33], others migrate shorter distances, and some remain as year-round residents in their nesting areas [23]. They exhibit dispersal movements and responses to resources that result in individuals using disparate locales during the course of their life cycle and mixing with birds from other geographic natal areas [23].…”
Section: Introductionmentioning
confidence: 99%
“…NA golden eagles exhibit a variety of migration strategies. Segments of the population undergo long annual migrations from Alaska and northern Canada [32,33], others migrate shorter distances, and some remain as year-round residents in their nesting areas [23]. They exhibit dispersal movements and responses to resources that result in individuals using disparate locales during the course of their life cycle and mixing with birds from other geographic natal areas [23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Golden Eagle habitat use have involved both migratory (e.g. Brodeur et al 1996, Alerstam 2001, McIntyre et al 2008, Duerr et al 2012, Johnston et al 2013, Moss et al 2014, Domenech et al 2015 and non-migratory birds (Marzluff et al 1997, Carrete et al 2000, McLeod et al 2002b, Sergio et al 2006, Tapia et al 2007, Sandgren et al 2014, Watson et al 2014, Braham et al 2015, Poessel et al 2016, Miller et al 2017, Tracey et al 2018. Later studies have benefitted from GPS telemetry (L opez-L opez 2016).…”
mentioning
confidence: 99%
“…First-year Golden Eagles showed great variation in space use in winter. Home ranges and core use areas we calculated tended to be larger than those reported for non-migrant populations (Marzluff et al 1997, Braham et al 2015, Poessel et al 2016, but were more similar to those of other migrant populations (Miller 2012, Domenech et al 2015). Home ranges we measured also tended to be larger than those of older, territorial birds (Marzluff et al 1997, Braham et al 2015, Poessel et al 2016, and more similar to reported home range size for younger eagles (Weston et al 2013).…”
Section: Discussionsupporting
confidence: 71%
“…Other studies which analyzed land cover change with higher resolution land cover data have been able to detect small yet significant changes (Xiubin 1996, Lindsay et al 2016, Tapia et al 2017). North America in winter (Harmata 2002, McIntyre 2012, Domenech et al 2015. Work in other systems has shown the relevance of carry over effects on avian demography (Webster 2002, Boulet and Norris 2006, Both et al 2010, Newton 2004.…”
Section: Land Cover Habitat Associations Over Time Winter Home Rangementioning
confidence: 99%